2013
DOI: 10.1103/physrevb.88.134525
|View full text |Cite
|
Sign up to set email alerts
|

Doping evolution of Zhang-Rice singlet spectral weight: A comprehensive examination by x-ray absorption spectroscopy

Abstract: The total spectral weight S of the emergent low-energy quasipaticles in high-temperature superconductors is explored by x-ray absorption spectroscopy. In order to examine the applicability of the Hubbard model, regimes that cover from zero doping to overdoping are investigated. In contrast to mean field theory, we found that S deviates from linear dependence on the doping level p. The slope of S versus p changes continuously throughout the whole doping range with no sign of saturation up to p = 0.23. Therefore… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 25 publications
(39 reference statements)
4
25
0
Order By: Relevance
“…While the valence of Cu remains 2 + (3 d 9 ) with hole doping, there is a clear emergence of a ligand hole state (3 d 9 L ) on the oxygen site, which is important for Cooper pairing4243. Detailed examination of the bulk cuprates have shown that this peak on both the Cu L -edge and O K -edge track directly with doping of the CuO 2 plane4445, which can be altered in the bulk by changing oxygen stoichiometry31, replacing Y with Ca4647, or doping at Cu sites48. Figure 3(a) shows the evolution of the polarization dependent Cu L -edge with increasing N together with a comparison to a thicker YBCO superlattice with bulk like absorption.…”
Section: Resultsmentioning
confidence: 99%
“…While the valence of Cu remains 2 + (3 d 9 ) with hole doping, there is a clear emergence of a ligand hole state (3 d 9 L ) on the oxygen site, which is important for Cooper pairing4243. Detailed examination of the bulk cuprates have shown that this peak on both the Cu L -edge and O K -edge track directly with doping of the CuO 2 plane4445, which can be altered in the bulk by changing oxygen stoichiometry31, replacing Y with Ca4647, or doping at Cu sites48. Figure 3(a) shows the evolution of the polarization dependent Cu L -edge with increasing N together with a comparison to a thicker YBCO superlattice with bulk like absorption.…”
Section: Resultsmentioning
confidence: 99%
“…The question is whether V/U can reach and go beyond the transition point. Recent x-ray absorption spectra [49] show that with increasing doping the doped holes start entering the Cu 3d states, hence the effective local U decreases (while the longer-ranged V is less influenced). Therefore, thé 2 2CDW phase is expected to be realized in the overdoped regime, in consistency with the experimental observation.…”
Section: Discussionmentioning
confidence: 99%
“…The technique is similar to that performed in Ref. [32]. The energy resolution of the monochromator was set to *0.2 eV for the Fe L edge.…”
Section: X-ray Absorption Spectroscopy (Xas)mentioning
confidence: 99%